k = 1 ∑ ∞ ( 3 k − 2 k ) ( 3 k + 1 − 2 k + 1 ) 6 k = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You can make this a cleanly telescoping sum if instead of 3 k and 3 k + 1 in the numerators, you use 2 k and 2 k + 1 .
Problem Loading...
Note Loading...
Set Loading...
S = k = 1 ∑ ∞ ( 3 k − 2 k ) ( 3 k + 1 − 2 k + 1 ) 6 k = k = 1 ∑ ∞ ( 3 k − 2 k 2 k − 3 k + 1 − 2 k + 1 2 k + 1 ) = 3 − 2 2 = 2 By partial fraction decomposition